Bonjour merci de m aider a faires ces exercices
Developpe et reduis les expressions suivantes:

A=3(x+1)(x-5)
B=2(-3-t)(t-7)
C= -(y+5)(3y-6)
D= x(2x-5)(2-x)
E=3(2x-6) - (3-5x)
F=(5-2y)-(-3y+7)
G=4(6+z)+(z-3)(2-z)
H=(2t-5)(3t+2)-(t au carre+6)
I= 3(-2x+5)+(-2x+5)(x-3)
J=(2a-5)(3-4a) -2(5-a)
K= -(3-4z)(z-2)
l= -5r(2-3r)+(-r-2)(2r+5)

1

Réponses

2014-03-11T10:50:03+01:00
Salut :)

A = 3(x + 1)(x - 5)
A = 3((x) x (x) + (x) x (-5) + 1 x (x) + 1 x (-5))
A = 3(x² - 5x + x - 5)
A = 3(x² - 4x - 5)
A = 3 x (x²) + 3 x (-4x) + 3 x (-5)
A = 3x² - 12x - 15

B = 2(-3 - t)(t - 7)
B = 2(-3t + 21 - t² + 7t)
B = 2(-t² + 4t + 21)
B = -2t² + 8t + 42

C = - (y + 5)(3y - 6)
C = - (3y² - 6y + 15y - 30)
C = -3y² + 6y - 15y + 30
C = -3y² - 9y + 30

D = x(2x - 5)(2 - x)
D = x(4x - 2x² - 10 + 5x)
D = 4x² - 2x⁴ - 10x + 5x²
D = -2x⁴ + 9x² - 10x

E = 3(2x - 6) - (3 - 5x)
E = 6x - 18 - 3 + 5x
E = 11x - 21
 
F = (5 - 2y) - (-3y + 7)
F = 5 - 2y + 3y - 7
F = y - 2

G = 4(6 + z) + (z - 3)(2 - z)
G = 24 + 4z + 2z - z² - 6 + 3z
G = -z² + 9z + 18

H  = (2t - 5)(3t + 2) - (t² + 6)
H = 6t² + 4t - 15t - 10 - t² - 6
H = 5t² - 9t - 16

I = 3(-2x + 5) + (-2x + 5)(x - 3)
I = -6x + 15 + -2x² + 6x + 5x - 15
I = -2x² + 5x

J = (2a - 5)(3 - 4a) - 2(5 - a)
J = 6a - 8a² - 15 + 20a - 10 + 2a
J = -8a² + 28a - 25

K = -(3 - 4z)(z - 2)
K = - (3z - 6 - 4z² + 8z)
K = -3z + 6 + 4z² - 8z
K = 4z² - 11z + 6

l = -5r(2 - 3r) + (-r - 2)(2r + 5)
I = -10r + 15r² - 2r² - 5r - 4r - 10
I = 13r² - 19r - 10

J'espère t'avoir aidé(e)! :)